MUSLIM TATAR DI POLANDIA: PENCARIAN IDENTITAS DAN INTEGRASI DALAM KONTEKS MULTIKULTURALISME EROPA - noer syo im; Prof. Dr. H. Abd A’la, M.Ag (Qolamuna : Jurnal Studi Islam, 2024)
One of the oldest Muslim communities in Europe, the Tatar minority in Poland struggles to preserve its cultural and religious identity while assimilating into a largely Christian culture. This study looks at how they defend minority rights, celebrate their culture, and educate others in an effort to maintain their identity. The Polish government's support for integration and its programs that foster cultural variety are also examined. An examination of secondary data and a review of the literature were part of the qualitative methodology. The study's findingsdemonstrate that, despite advancements, prejudice and preconceptions persist, and young people still struggle to stay true to who they are. Therefore, to foster integration and promote cultural variety in Poland and throughout Europe, ongoing efforts in education, youth participation, civil society collaboration, and inclusive policies are required. Keywords : Tatar Muslims, Poland, Multiculturalism